PERANiKEPEMIMPINAN DALAM ORGANISASI DI SDN 2 TRISOBO KECAMATAN BOJA - Era Dhika Safitri; Noor Miyono (STKIP Subang, 2023)
Leaders in an organization have an important role in directing and influencing their subordinates. Without people managing and directing an organization, the organization can undoubtedly achieve its goals in accordance with its vision and mission. Therefore, a leader is needed to be able to manage and regulate the organization to achieve its goals. This research aims to examine the importance of leadership in organizations using a literature approach applied at SDN 2 Trisobo, Boja District. This type of research is research with a literature study approach which is carried out by finding theoretical references that are appropriate to the cases obtained. A leader is a positive and confident person who has a vision, mission and high ethical values, with the ability to convey ideas and is able to encourage and relate well to other people. Leadership will be a determining factor for success in an organization. This is because leadership is the central point of significant change in an organization, leadership becomes a personality that has an impact and leadership is the art of creating organizational conformity and stability.